1998
DOI: 10.1002/(sici)1099-0992(199809/10)28:5<697::aid-ejsp889>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Responding to negative social identity: a taxonomy of identity management strategies

Abstract: Taken from literature on social identity theory and social comparison theory, 12 strategies of identity management were identified as possible responses to negative social identity. A taxonomy with two orthogonal axes is proposed as theoretical organization of these diverse strategies. While the first axis considers responses as being either individual or collective, the second axis refers to the distinction between behaviours and cognitions. It is assumed that the German unification process implied a lower st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
189
1
19

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(214 citation statements)
references
References 23 publications
5
189
1
19
Order By: Relevance
“…The first two strategies represent the extremes of Tajfel's social mobility-social change dimension (Tajfel, 1978) and also represent the most investigated strategies of dominant and non-dominant groups. Individualization and re-categorization, on a higher level, represent strategies by which individuals either shift from a social to personal self-categorization or from an ingroup category to an inclusive category consisting of both ingroup and outgroup (see Blanz et al, 1998). Within the context of the present study, the latter two strategies represent a cognitive shift by which the participants avoid interracial comparisons.…”
Section: Go Vernm En T-led Trans Form a Fion Processmentioning
confidence: 85%
“…The first two strategies represent the extremes of Tajfel's social mobility-social change dimension (Tajfel, 1978) and also represent the most investigated strategies of dominant and non-dominant groups. Individualization and re-categorization, on a higher level, represent strategies by which individuals either shift from a social to personal self-categorization or from an ingroup category to an inclusive category consisting of both ingroup and outgroup (see Blanz et al, 1998). Within the context of the present study, the latter two strategies represent a cognitive shift by which the participants avoid interracial comparisons.…”
Section: Go Vernm En T-led Trans Form a Fion Processmentioning
confidence: 85%
“…Social identity theory assumes that a disadvantaged ingroup status results in an unsatisfactory or negative social identity (Tajfel & Turner, 1979). Because people strive for a positive social identity, members of low-status groups may leave their groups to restore their positive social identity (Blanz et al, 1998;Tajfel, 1978). Consistent with this prediction, this study found that to the extent that local senior executives perceive the local staff to be incompetent (thus, identification with them represents a negative social identity), these executives tend to think about leaving the group (i.e., have higher levels of turnover intentions).…”
Section: Discussionmentioning
confidence: 99%
“…In this strategy, privileged members of a low-status group make a career for themselves without changing the status relations between the low-and the high-status groups by identifying with the high-status group and disidentifying with, or in a sense, "exiting" from (Hirschman, 1970), the low-status group (cf. Blanz, Mummendey, Mielke, & Klink, 1998). Consistent with this reasoning, Tajfel and Turner (1979) suggested that a disadvantageous social identity may result in intentions to leave a low-status group.…”
Section: Role Of Identification With the Local Staffmentioning
confidence: 93%
“…Tajfel andTurner (1979, 1986) distinguished three identity management strategies: individual mobility (i.e., the individual's position is changed whilst the status relations between the comparison groups remain unchanged); creativity strategies (i.e., comparison references are changed in one or the other way so that negative comparison results become less important) and social competition (i.e., to seek social change). Based on self-categorisation theory (Turner, Hogg, Oakes, Reicher, & Wetherell, 1987) an additional strategy was introduced by Blanz, Mummendey, Mielke, and Klink (1998) which is called individualisation. The notion of individualisation essentially describes the shift from social to personal self-categorisation, i.e., people attribute more importance to their personal than to their social identity.…”
Section: Ideal Selves From a Sit Perspectivementioning
confidence: 99%